ANALISA KEBUTUHAN ENERGI MOTOR LISTRIK PADA PROTOTYPE MOBIL HYBRID - Sueb Herdianto; Mardjuki Mardjuki; Suprayogi Suprayogi (University of Merdeka Malang, 2016)
Environmental pollution and fuel savings are a significant problem for the life of the future. The need-based electric vehicle that can replace the use of energy. Therefore, the hybrid vehicle is a vehicle that is right for a solution to reduce environmental pollution and save fuel. In addition to the hybrid vehicle has several sections, among which the use of electric motors. The aim is to meet the energy needs of a DC electric motor as a vehicle drive hybrid cars, so as to determine the electric motor in accordance with the needs and characteristics of the hybrid car. Besides the basic principle is to try to design a machine that relate to the needs of its specifications. Then obtained the results of research on the use of current and voltage when the gas pedal is pressed / stamped starts from 10o - 50o can be concluded that the more the gas pedal board, the increasing speed with an electric motor rotation of 794 (rpm), 47.56 voltage (volts ), the current 20.3 (ampere), then the required power DC electric motor that is equal to 984.75 (watts).